2022
DOI: 10.3389/fcimb.2022.956112
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric analysis of host and parasite elements in new world tegumentary leishmaniasis

Abstract: Tegumentary leishmaniasis is a tropical disease caused by protozoa of the genus Leishmania. Clinically, the disease presents a broad spectrum of symptoms, the mechanisms underlying the development of lesions remaining to be fully elucidated. In the present work, we performed a correlation and multiparametric analysis to evaluate how parasite- and host-related aspects associate with each other, and with the different clinical manifestations of tegumentary leishmaniasis. This cross-sectional study involved 75 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, collaborations with other dermatology centers to increase the database of other dermatoses may be a possible solution. It is important to expand the database to include CL lesions and other skin diseases caused by various Leishmania species found in other countries, as our study indicates that the lesions are predominantly caused by L. braziliensis, and in some cases, by L. amazonensis and L. guyanensis [60,61]. It is noteworthy that Old World CL lesions differ from New World lesions, which may progress to hyperkeratotic plaques.…”
Section: Discussionmentioning
confidence: 90%
“…However, collaborations with other dermatology centers to increase the database of other dermatoses may be a possible solution. It is important to expand the database to include CL lesions and other skin diseases caused by various Leishmania species found in other countries, as our study indicates that the lesions are predominantly caused by L. braziliensis, and in some cases, by L. amazonensis and L. guyanensis [60,61]. It is noteworthy that Old World CL lesions differ from New World lesions, which may progress to hyperkeratotic plaques.…”
Section: Discussionmentioning
confidence: 90%
“…However, the specificity is low, and false-positive results may occur (van Griensven and Diro, 2019;Scarpini et al, 2022). In recent years, some studies have found that qPCR analysis of mitochondrial DNA minicircle network (kDNA) based on the characteristics of Leishmania genus has high sensitivity and specificity, and can thus be useful for quantitative detection of pan-Leishmania (Ceccarelli et al, 2020;de Carvalho et al, 2022;Mota et al, 2022). However, this technique is expensive and has not been used for routine clinical testing.…”
Section: Discussionmentioning
confidence: 99%
“…In an area of L braziliensis transmission in the northeast region of Brazil, RCL was found in 4% of the cases, usually more than 5 years after the treatment and cure of primary CL [ 1 ]. Others have found that although the parasite load was similar in lesions from RCL patients infected with L braziliensis and with primary CL (PCL), it was higher in the blood of RCL patients compared with PCL patients [ 4 ]. In CL caused by Leishmania major , recurrence was associated with female gender, number of lesions, and longer duration of therapy of PCL, but it is not known which factors influence the occurrence of RCL in areas of L braziliensis transmission.…”
mentioning
confidence: 99%